Empowering people with severe mental illness a practical guide - Linhorst, Donald M., 1956- (Oxford University Press, 2006)
"Presents a model of empowerment and then applies it to seven areas that the have potential to empower people with severe mental illness, including treatment planning, housing, employment, and others. Provides practitioners, administrators, and policymakers with specific guidelines and actions to promote empowerment"--Provided by publisher.